STATE OF OXIDATIVE METABOLISM IN HEART AND SKELETAL MUSCLE TISSUES OF RATS UNDER CONTINUOUS LIGHTING - Hilmutdinova, M.Sh.; Chebotar, L.D.; Cherno, V.S. (World of Medicine and Biology, 2021)
The article considers and compares the features of oxidative metabolism of cardiac and skeletal muscle tissue under the changed photoperiod conditions, influenced by continuous lighting. It is shown that under the conditions of continuous lighting in the studied tissues there is an imbalance in the “prooxidants-antioxidants” system, a shift of balance towards peroxidation processes, which is manifested in increased generation of reactive oxygen species, increased concentration of peroxide oxidation secondary products, decreased activity of some antioxidant enzymes in the cardiac muscle tissue. In its turn, in the skeletal muscle tissue, a shift in balance is manifested in the decreased activity of some antioxidant enzymes.